2019
DOI: 10.1080/22423982.2018.1517581
|View full text |Cite
|
Sign up to set email alerts
|

The need for community-led, integrated and innovative monitoring programmes when responding to the health impacts of climate change

Abstract: The need for community-led, integrated and innovative monitoring programmes when responding to the health impacts of climate change,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 73 publications
1
30
0
1
Order By: Relevance
“…In climate research, positivist forms of knowledge have previously been prioritised at the expense of experiential knowledge, which can result in the creation of knowledge both detached from its local context and embedded in Western scientific epistemologies that are shaped by histories of colonisation (Conway et al, 2019). Engaging citizens and rightsholders in research and decision-making is one way to challenge these in-grained hierarchies of knowledge and their problematic manifestations in the creation of knowledge relevant to climate change (Sawatzky et al, 2018;Kipp et al, 2019;van Bavel et al, 2020). Participatory processes, including collaborative, co-productive, and cross-cultural methods for knowledge production, can provide more place-based and contextual nuance to previously positivist climate and environmental modelling processes (Lynam et al, 2007;Nakashima et al, 2012;Alshaikh, 2013;Crate et al, 2019;Gotts et al, 2019;Mach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In climate research, positivist forms of knowledge have previously been prioritised at the expense of experiential knowledge, which can result in the creation of knowledge both detached from its local context and embedded in Western scientific epistemologies that are shaped by histories of colonisation (Conway et al, 2019). Engaging citizens and rightsholders in research and decision-making is one way to challenge these in-grained hierarchies of knowledge and their problematic manifestations in the creation of knowledge relevant to climate change (Sawatzky et al, 2018;Kipp et al, 2019;van Bavel et al, 2020). Participatory processes, including collaborative, co-productive, and cross-cultural methods for knowledge production, can provide more place-based and contextual nuance to previously positivist climate and environmental modelling processes (Lynam et al, 2007;Nakashima et al, 2012;Alshaikh, 2013;Crate et al, 2019;Gotts et al, 2019;Mach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Community-based monitoring (CBM) is often considered a promising strategy to improve monitoring of, and local adaptation to, environmental change [52][53][54]. CBM is an approach whereby groups collaborate to track and respond to issues of common community concern [52].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the landscape of existing community-based monitoring programs in the North, Kipp et al conducted a review and environmental scan to identify, characterize, and contextualize existing environmental and health monitoring programs [20]. This review identified elements that are necessary to support climate-related health surveillance, including the need for strong community leadership, the inclusion of environment and human health, and the incorporation of innovative technology.…”
Section: Innovations In Community Health Systemsmentioning
confidence: 99%